Effect of surface treatment and shear flow on biofilm formation over materials employed in space water storage and distribution systems - Avgoulas, Dimitrios I.; Petala, Maria; Briandet, Romain; Dergham, Yasmine; Noirot-Gros, Marie-Francoise; Konstantinidis, Avraam; Kostoglou, Margaritis; Karapantsios, Thodoris D. (Frontiers in Materials, 2024)
The prolonged duration of future manned space missions conceals potential threats associated with microbial contamination. Such closed environments are susceptible to formation of complex biofilm communities, where microorganisms can thrive and further evolve. The objective of this study was to evaluate the impact of surface type, surface treatment and shear stress on biofilm formation in water facilities. To that aim, the ability of Pseudomonas fluorescens SBW25 to adhere on three space applications related materials, including passivated (SS) and both passivated and electropolished (SSEP) stainless steel, as well as Ti-6Al-4V (Ti) alloy was studied under stagnant and shear stress conditions after 24 h of exposure. Results indicated that surface type strongly affects bacterial adhesion under the same conditions. Surface coverage during static experiments was in the following order: SS > Ti > SSEP, while SS exhibited a fourfold surface coverage compared to SSEP highlighting the significance of surface treatment. Moreover, SS and Ti stimulate the formation of several microcolonies and their growth. On the other hand, the application of shear stress diminished bacterial attachment to the studied materials, the degree of which relied on the material type. In this case, bacterial settlement on SS and Ti was dependent on the surface texture, implying that surface roughness may also play an important role in cell adhesion under shear conditions. Furthermore, the metallic surfaces did not hinder bacterial attachment when silver ions were previously deposited on their surface. The deposition that occurs on metallic surfaces when in contact with water disinfected with silver ions, for example, during space missions, highlights its impact on the loss of disinfection capacity of silver ions.